2012
DOI: 10.1186/1752-1947-6-25
|View full text |Cite
|
Sign up to set email alerts
|

Cleidocranial dysplasia presenting with retained deciduous teeth in a 15-year-old girl: a case report

Abstract: IntroductionCleidocranial dysplasia is a rare congenital defect of autosomal dominant inheritance caused by mutations in the Cbfa1 gene, also called Runx2, located on the short arm of chromosome 6. It primarily affects bones which undergo intramembranous ossification. This condition is of clinical significance to dentistry due to the involvement of the facial bones, altered eruption patterns and multiple supernumerary teeth.Case presentationOur patient, a 15-year-old Indian girl, presented with the typical fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 9 publications
(10 reference statements)
0
7
0
Order By: Relevance
“…A study ( 37 ) of 205 patients with harelip and cleft palate found a frequency of supernumerary teeth of 11.7%. Several other studies ( 38 , 39 ) have observed cases of cleidocraneal dysplasia with the presence of supernumerary teeth. The gene responsible for cleidocraneal dysplasia is the RUNX2 and mutations of this gene could explain the existing correlation between the syndrome and the presence of supernumerary teeth ( 40 ).…”
Section: Syndromes Associated With Supernumerary Teethmentioning
confidence: 86%
“…A study ( 37 ) of 205 patients with harelip and cleft palate found a frequency of supernumerary teeth of 11.7%. Several other studies ( 38 , 39 ) have observed cases of cleidocraneal dysplasia with the presence of supernumerary teeth. The gene responsible for cleidocraneal dysplasia is the RUNX2 and mutations of this gene could explain the existing correlation between the syndrome and the presence of supernumerary teeth ( 40 ).…”
Section: Syndromes Associated With Supernumerary Teethmentioning
confidence: 86%
“…As such, one of the basic problems in orthodontic therapy of CCD is their correct diagnosis and removal. It is worth noting that of the five reports described above, only in one publication [13] did the researchers use Cone Beam Computed Tomography to plan treatment. In this author’s case, the CCD treatment plan and surgical-orthodontic therapy was preceded by CBCT.…”
Section: Discussionmentioning
confidence: 99%
“…The difference lies in the orthodontic appliances used to expose the retained teeth. The use of both fixed [13,14] and removable appliances were described [12,15], and a removable device was used in our own case. However, it is important to emphasize the fact that in such therapy, working directly with the patient is indispensable, as such cooperation strongly affects the final result – the lifespan of the appliance and the patient’s fixing of the elastic traction on their own significantly affects the outcome of the therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations